Atividade tóxica de isolados de Bacillus Thuringiensis a larvas de Aedes Aegypti (l.) (diptera: culicidae) - Costa, Juliana R V da; Rossi, Juliana R; Marucci, Suzana C; Alves, Eliane C da C; Volpe, Haroldo X L; Ferraudo, Antonio S [UNESP]; Lemos, Manoel V F; Desidério, Janete A (Sociedade Entomológica do Brasil, 2010)
Aedes aegypti (L.), the main vector of dengue fever in Brazil, has been controlled with the use of massive chemical products, contributing to the development of resistance and decreasing the insect control efficiency. The control of dipterans with bioinsecticides based on Bacillus thuringiensis has been satisfactory, due to the production of insecticidal proteins denominated Cry (crystal), Cyt (cytolytic) toxins and Chi (chitinase), and to the synergistic effects among them. The present work aimed to select B. thuringiensis isolates efficient against A. aegypti larvae. A bacterial collection containing 1,073 isolates of B. thuringiensis, obtained from different locations of Brazilian territory, had the DNA isolated and submitted to PCR amplifications using specific primers for cry4Aa, cry4Ba, cry11Aa, cry11Ba, cyt1Aa, cyt1Ab, cyt2Aa and chi genes. For the LC50 and LC90 determination, the entomopathogenic isolates were evaluated by selective and quantitative bioassays. Only 45 isolates (4.2%) presented amplicons for the cry and cyt genes. The chi gene sequence was detected in 25 (54.3%) of those isolates. From the 45 isolates submitted to the selective bioassays, 13 caused 100% mortality of A. aegypti larvae. The identification of cry, cyt and chi genes of B. thuringiensis and the toxicity analysis on A. aegypti led to the selection of a set of isolates that have the potential to be used in the formulation of new bioinsecticides.
Toxic activity of Bacillus Thuringiensis isolates to Aedes Aegypti (l.) (diptera: culicidae) larvae
Keywords: Biological control; Cry; Cyt; Chitinase; Dengue fever